The transcription factor DUX4 orchestrates translational reprogramming by broadly suppressing translation efficiency and promoting expression of DUX4-induced mRNAs. - Danielle C Hamm; Ellen M Paatela; Sean R Bennett; Chao-Jen Wong; Amy E Campbell; Cynthia L Wladyka; Andrew A Smith; Sujatha Jagannathan; Andrew C Hsieh; Stephen J Tapscott (PLoS Biology, 2023)
Translational control is critical for cell fate transitions during development, lineage specification, and tumorigenesis. Here, we show that the transcription factor double homeobox protein 4 (DUX4), and its previously characterized transcriptional program, broadly regulates translation to change the cellular proteome. DUX4 is a key regulator of zygotic genome activation in human embryos, whereas misexpression of DUX4 causes facioscapulohumeral muscular dystrophy (FSHD) and is associated with MHC-I suppression and immune evasion in cancer. We report that translation initiation and elongation factors are disrupted downstream of DUX4 expression in human myoblasts. Genome-wide translation profiling identified mRNAs susceptible to DUX4-induced translation inhibition, including those encoding antigen presentation factors and muscle lineage proteins, while DUX4-induced mRNAs were robustly translated. Endogenous expression of DUX4 in human FSHD myotubes and cancer cell lines also correlated with reduced protein synthesis and MHC-I presentation. Our findings reveal that DUX4 orchestrates cell state conversion by suppressing the cellular proteome while maintaining translation of DUX4-induced mRNAs to promote an early developmental program.